Variation in platelet count with gestational age, weight and sex in hospitalized newborns - Dr.Rabindran; Dr.Hemant Parakh; Dr.Ramesh J K; Dr.Prashant Reddy (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Platelet count & CRP are diagnostic markers of neonatal sepsis. Though the platelet count remains the same throughout the neonatal period, variations in platelet count have been noted based on gestational age, weight & sex of neonates. Beside other hematological findings, changes in platelet count induced by neonatal sepsis have been the focus of many studies. Objective: To analyze the variation in platelet count with gestational age, weight and sex in hospitalized newborns. Methods: This is a retrospective case analysis of 533 neonates between January-2012 to December-2014. The parameters examined were Baseline Platelet Count, Change In Platelet Count, (Baseline Platelet Count- Change In Platelet Count)/ Baseline Platelet Count, Platelet Nadir, Incidence, Duration & Severity of Thrombocytopenia. Statistical Analysis: All data were collected in validated preformatted proforma sheet & analysed using appropriate statistical methods. Results: 533 babies were studied. About 21.2% had Culture negative sepsis, 9.75% had culture positive sepsis & 69.04% had no sepsis. No difference in any platelet parameter was noted between female & male babies. The prevalence of early onset sepsis in our study was 17.44% & late onset sepsis was 13.50%. Significant variations of all platelet indices were noted among lower gestational age babies. Significant variations in the Incidence, Prevalence & duration of thrombocytopenia were noted depending on the weight of the baby. Conclusion: The baseline platelet count of the neonates remains uniform irrespective of sex, weight or gestational age. There are quantitative differences in the platelet response based on weight and gestational age